2009
DOI: 10.1111/j.1600-0706.2009.17369.x
|View full text |Cite
|
Sign up to set email alerts
|

Predator effects on aquatic community assembly: disentangling the roles of habitat selection and post‐colonization processes

Abstract: Top predators are known to play an important role in the assembly of communities via two mechanisms: (1) by altering the colonization (or emigration) patterns of prey through behavioral habitat selection, and (2) by altering vital rates (e.g. mortality, birth) of prey after colonization. While both these mechanisms act to determine assembly, research has focused on either their combined overall effects (confounding them), or examined them singly. As a result, it remains unclear how these mechanisms act to sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 45 publications
(58 reference statements)
4
104
2
Order By: Relevance
“…In support of this hypothesis, recent field experiments have shown that in regions of Scandinavia with high densities of invertivorous fish, fish exclusion can lead to increases in grazer density and decreases in algae (Moksnes et al 2008, Eriksson et al 2009, Baden et al 2010, Sieben et al 2011). This parallels evidence for similar fish-invertebrate-periphyton trophic cascades in freshwater benthic systems (Power 1990, Bronmark et al 1992, Martin et al 1992, Vonesh et al 2009.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In support of this hypothesis, recent field experiments have shown that in regions of Scandinavia with high densities of invertivorous fish, fish exclusion can lead to increases in grazer density and decreases in algae (Moksnes et al 2008, Eriksson et al 2009, Baden et al 2010, Sieben et al 2011). This parallels evidence for similar fish-invertebrate-periphyton trophic cascades in freshwater benthic systems (Power 1990, Bronmark et al 1992, Martin et al 1992, Vonesh et al 2009.…”
Section: Introductionsupporting
confidence: 55%
“…In our study, we considered only the effect that fish predation may have on grazer abundance, but predator presence can also change the habitat choices (Wellborn et al 1996, Resetarits 2001, Vonesh et al 2009) and consumption rates (Schmitz et al 1997, Duffy et al 2005) of existing grazers. For tube-building amphipods that use the macroalgae they consume as a refuge (e.g.…”
Section: Generality Of the Negative Relationship Between Grazing Ratementioning
confidence: 99%
“…Although such a proposition that is daunting and rarely realized (Cronin and Reeve 2005), several recent studies can be used as models for future investigations (e.g., Vonesh and Osenberg 2003, Resetarits 2005, Vonesh et al 2009, Kraus and Vonesh 2010.…”
Section: Quantifying Remote Effectsmentioning
confidence: 99%
“…By changing rates of immigration, either through altering the number of active migrants Wooster 1994, McIntosh et al 2002), through habitat selection behavior (Resetarits 2005, Resetarits and Binckley 2009, Kraus and Vonesh 2010, or both, remote predators could readily alter the importance of mass effects for determining community composition . The effects of predators on habitat selection by prey can have persistent effects on local community structure even in the presence of strong post-colonization processes (Vonesh et al 2009). Recent work reveals the potential for remote effects to be important in this context, as habitat selection creates spatial contagion of predator effects into predator-free patches located near predator-containing patches (Resetarits and Binckley 2009).…”
Section: Community-level Dynamicsmentioning
confidence: 99%
“…Bird species that combined to contribute greater than or equal to 50 per cent of the community dissimilarities (based on SIMPER analysis). rspb.royalsocietypublishing.org Proc R Soc B 280: 20130762 demographic rates post-colonization [51]. Because our study spanned one breeding season, the observed community changes should predominantly be the result of communitywide alteration in avian habitat selection under heightened perception of predation risk.…”
Section: Discussionmentioning
confidence: 99%